Gardnerella vaginalis, Fannyhessea vaginae, and Prevotella bivia Strongly Influence Each Other's Transcriptome in Triple-Species Biofilms - Sousa, Lúcia G. V.; Novak, Juliano; França, Angela; Muzny, Christina A.; Cerca, Nuno (Springer Nature, 2024)
Bacterial vaginosis (BV), the most common vaginal infection worldwide, is characterized by the development of a polymicrobial biofilm on the vaginal epithelium. While Gardnerella spp. have been shown to have a prominent role in BV, little is known regarding how other species can influence BV development. Thus, we aimed to study the transcriptome of Gardnerella vaginalis, Fannyhessea vaginae, and Prevotella bivia, when growing in triple-species biofilms. Single and triple-species biofilms were formed in vitro, and RNA was extracted and sent for sequencing. cDNA libraries were prepared and sequenced. Quantitative PCR analysis (qPCR) was performed on the triple-species biofilms to evaluate the biofilm composition. The qPCR results revealed that the triple-species biofilms were mainly composed by G. vaginalis and P. bivia was the species with the lowest percentage. The RNA-sequencing analysis revealed a total of 432, 126, and 39 differentially expressed genes for G. vaginalis, F. vaginae, and P. bivia, respectively, when growing together. Gene ontology enrichment of G. vaginalis downregulated genes revealed several functions associated with metabolism, indicating a low metabolic activity of G. vaginalis when growing in polymicrobial biofilms. This work highlighted that the presence of 3 different BV-associated bacteria in the biofilm influenced each other’s transcriptome and provided insight into the molecular mechanisms that enhanced the virulence potential of polymicrobial consortia. These findings will contribute to understand the development of incident BV and the interactions occurring within the biofilm.